The Role of ARID5B in Acute Lymphoblastic Leukemia and Beyond - Wang, Peiqi; Deng, Yun; Yan, Xinyu; Zhu, Jianhui; Yin, Yuanyuan; Shu, Yang; Bai, Ding; Zhang, Shouyue; Xu, Heng; Lu, Xiaoxi (Frontiers in Genetics, 2020)
Pediatric acute lymphoblastic leukemia (ALL) is the most common malignancy in children with distinct characteristics among different subtypes. Although the etiology of ALL has not been fully unveiled, initiation of ALL has been demonstrated to partly depend on genetic factors. As indicated by several genome wide association studies (GWASs) and candidate gene analyses, ARID5B, a member of AT-rich interactive domain (ARID) protein family, is associated with the occurrence and prognosis of ALL. However, the mechanisms by which ARID5B genotype impact on the susceptibility and treatment outcome remain vague. In this review, we outline developments in the understanding of ARID5B in the susceptibility of ALL and its therapeutic perspectives, and summarize the underlying mechanisms based on the limited functional studies, hoping to illustrate the possible mechanisms of ARID5B impact and highlight the potential treatment regimens.